Temporary cardiopulmonary bypass and isolated lung ventilation for tracheal stenosis and reconstruction. - Chiu, C.L.; Teh, B.T.; Wang, C.Y. (Oxford University Press, 2003)
A 27-yr-old lady with a past history of prolonged ventilation presented with worsening respiratory distress caused by tracheal stenosis. She required urgent tracheal resection and reconstruction. Because of the risk of an acute respiratory obstruction, spinal anaesthesia was used to establish cardiopulmonary bypass by cannulating the femoral artery and femoral vein. Adequate gas exchange was possible with full flow rate. Thoracotomy was then carried out to mobilize the left main bronchus. After successfully securing an airway by intubation of the left main bronchus, cardiopulmonary bypass was discontinued and tracheal resection and anastomosis was done under conventional one lung anaesthesia.